in european style - Grigoryeva, Elena (project baikal, 2018)
The Italian triptych by Leonid Salmin brings us into the interior of the southern cities of Italy, where the spaces are narrow, having been fully inhabited by citizens for a long time, and where bed sheets flutter like flags of privacy above the chairs and tables set out on the pedestrian way and even on the roadway (114). After the hot Sicily and Naples we are carried away by Olga Smirnova, a wonderful storyteller, to a fairy tale of foggy London (120) and have a five o'clock tea together with a millionaire in Chelsea. Then comes a big article by Georgi Stanishev about Rudy Ricciotti, an architect whose interior of the city blends into the interior of the building, and whose bridges link the fragments of the city like interior doors.
Keywords: interior of the city; interior of the building; Italy; London